ANALISIS KEUNTUNGAN PETANI PADA USAHATANI JAGUNG HIBRIDA DI DESA DAENAA KECAMATAN LIMBOTO BARAT KABUPATEN GORONTALO - Laiya, Risnawati H; Murtisari, Amelia; Boekoesoe, Yuriko (AGRINESIA : Jurnal Ilmiah Agribisnis, 2017)
This study aims to analyze: 1) To know the cost structure of hybrid corn farming in Daenaa Village, West Limboto District, Gorontalo Regency, 2) Analyze the income of hybrid maize farm in Daenaa Village, West Limboto District, Gorontalo Regency. This research was conducted in Daenaa Village, West Limboto District, Gorontalo District from July to August of 2017. The method used was survey method that is data collection based on interview and observation. The sampling technique was done by using systematic sampling method. Namely sampling technique from a sequence of lists in a particular order where in this study the population consists of 750 people and taken from a multiple of 25 so that the results obtained as many as 31 people. Types and data sources used in this study are primary data and secondary data. Data analysis used is farming analysis by calculating cost, revenue, and income. The results showed that 1). the cost structure of the maize farm in Daenaa Village is a fixed cost of Rp. 1.092.074 / farmer or Rp. 868.058 / ha and variable cost Rp.5.492.886 / farmer or Rp.4.366.139 / ha. 2). The average revenue received at the maize farm in Daenaa Village is Rp. 10.134.667 / farmer / ha. While the average income received is Rp. 3,549,718 / farmers or Rp.2.821.57 / ha.